Islam-based holistic learning management: Challenges and opportunities for private islamic university - Zaenal Abidin; Fitri Nurdianingsih (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The rapid transformation of education in the digital and global era requires approaches that not only emphasize cognitive achievement but also integrate moral and spiritual development, particularly in Islamic higher education. This study aims to analyze the implementation of Islamic-based holistic learning management in private Islamic universities in Jambi Province, focusing on how academic, moral, and spiritual dimensions are integrated, as well as identifying the challenges and opportunities encountered. This study employed a qualitative case study approach, with data collected through in-depth interviews, classroom observations, and curriculum document analysis, while triangulation techniques were used to ensure the validity and reliability of the findings. The results indicate that Islamic values-based holistic learning management enhances student engagement, motivation, and overall well-being by integrating values such as tawhid and ihsan into the learning process, while also emphasizing the need for curriculum reform that balances intellectual, character, and spiritual development. However, the study identifies several challenges, including limited technological infrastructure, insufficient human resource capacity, and resistance to change among educators. Overall, this study concludes that Islamic-based holistic learning management provides a relevant and effective approach to addressing contemporary educational challenges, although its successful implementation requires strong institutional commitment, investment in digital infrastructure, continuous professional development, and strengthened collaboration with communities and international partners.